2007
DOI: 10.1021/pr070366b
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Host Responses in HepG2 Cells during Dengue Virus Infection

Abstract: Dengue virus infection remains a public health problem worldwide. However, its pathogenic mechanisms and pathophysiology are still poorly understood. We performed proteomic analysis to evaluate early host responses (as indicated by altered proteins) in human target cells during dengue virus infection. HepG2 cells were infected with dengue virus serotype 2 (DEN-2) at multiplicity of infection (MOI) of 0.1, 0.5, and 1.0. Quantitative analyses of DEN-2 infection and cell death at 12, 24, and 48 h postinfection sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
41
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 40 publications
5
41
0
1
Order By: Relevance
“…Of these seven proteins, altered protein expression was confirmed by Western analysis for two proteins; elongation factor Tu (EF-Tu) mitochondrial precursor and vinculin. Altered GRP78 protein levels were not identified in this study (32). Using 2DGE and MS analysis, we successfully identified GRP78 as significantly upregulated in DENV-infected cells.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Of these seven proteins, altered protein expression was confirmed by Western analysis for two proteins; elongation factor Tu (EF-Tu) mitochondrial precursor and vinculin. Altered GRP78 protein levels were not identified in this study (32). Using 2DGE and MS analysis, we successfully identified GRP78 as significantly upregulated in DENV-infected cells.…”
Section: Discussionmentioning
confidence: 55%
“…The total number of spots detected was low and could be improved technically by cup loading rather than passive rehydration of IEF strips, use of a more sensitive protein stain, and fractionation of cell lysates to reduce protein complexity. A proteomic study of DENV-infected HepG2 cells identified 800 protein spots and 17 differentially expressed proteins, only 7 of which were altered by Ͼ2-fold, the cutoff used in our proteomic study (32). Of these seven proteins, altered protein expression was confirmed by Western analysis for two proteins; elongation factor Tu (EF-Tu) mitochondrial precursor and vinculin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of the chaperonin GroEL in the host could be due to the presence of misfolded or aggregated proteins under stress conditions. The elongation factors EF-Tu and EF-Ts have been found to bind tightly to the viral RNAdependent RNA polymerase and have a major function in the delivery of aminoacyl-tRNA (aa-tRNA) to the A site on the ribosome during the translation of mRNA into protein (18). In our study, the upregulation of EF-Ts in the GVE2-infected Geobacillus sp.…”
Section: Discussionmentioning
confidence: 73%
“…Proteomics approaches have become increasingly popular in studies to reveal the effects of viral infection on the cellular proteome (1,27). Comparative proteomic approaches coupling two-dimensional electrophoresis (2-DE) and mass spectrometry (MS) are widely used to analyze host responses in animals, humans, and plants during virus infection (18,19,20). The approaches effectively facilitate investigations of the molecular profiles of virus-infected cells (27).…”
mentioning
confidence: 99%